Photocatalytic synthesis of tetra-substituted furans promoted by carbon dioxide. Issue 1 (12th December 2021) - Tian, Ya-Ming; Wang, Huaiju; Ritu,; König, Burkhard
Abstract : A CO2 -promoted transition metal-free photocatalytic synthesis of tetra-substituted furan derivatives from 1, 3-diketones as the only starting material. Abstract : We report a simple protocol for the transition metal-free, visible-light-driven conversion of 1, 3-diketones to tetra-substituted furan skeleton compounds in carbon dioxide (CO2 ) atmosphere under mild conditions. It was found that CO2 could be incorporated at the diketone enolic OH position, which was key to enabling the cleavage of a C–O bond during the rearrangement of a cyclopropane intermediate. This method allows for the same-pot construction of two isomers of the high-value tetra-substituted furan scaffold. The synthetic scope and preliminary mechanistic investigations are presented.